EXISTING FEMINISM IN HELEN GARNER’S MONKEY GRIP - A, Delukman (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
Man and woman are created by God in equality position, but in many aspects of life, man reveals domination and discrimination to woman. The aim of the study is to investigate Helen Garner’s work, Monkey Grip (1977). The researcher focuses on the issue of feminism that exists in the novel. The researcher identifies feminism issues based on the two ways, they are behavior and language. Behavior of feminism includes the idea and the action. The idea means a wish or concept of the woman character to get freedom, then action is implementation of the idea. Language of feminism means how the woman expresses sexual desire in the novel. Moreover, this research uses sociological approach to see relation between the novel and society. The method used in this research is descriptive qualitative method. The primary data are taken by the novel Monkey Grip by Helen Garner and secondary data are taken by some journals, books, and articles. From the research, the researcher found that the woman character could stand without a husband. The woman character who gets discrimination by a man can leave her special friend. Furthermore, the woman character in this story talks about sexual desire freely and openly. The author of this novel tries to argue that it is not taboo to talk about sexual desire in the novel anymore. The research also reveals relation between the author and the novel where the author brings her experiences in her life into the novel, such as unhappy marriage. Moreover, this research is a kind of liberal feminism. Liberal feminism believe that woman have to be independent woman in private and public sphere.